Hue’s in the trap? Effects of colour, time of day, and weather on the use of pitfall traps for invertebrate surveys - Anne E. Goodenough; Hannah L. Baker; Feranmi Otitolaye; Frankie Wilson; Julia C. Webb (Journal of Insect Conservation, 2026)

Using non-invasive and minimally-invasive methods to inform conservation of terrestrial mammals: A review of novel techniques and new applications - Anne E. Goodenough; Samantha J. Perks (Journal for Nature Conservation, 2025)

Correction to: From tweets to tings: Dissimilarity in recorded species community between social media platforms and implications for resource-limited conservation - Adam G. Hart; Elliot Tripp; Anne E. Goodenough (Community Ecology, 2025)

From tweets to tings: Dissimilarity in recorded species community between social media platforms and implications for resource-limited conservation - Adam G. Hart; Elliot Tripp; Anne E. Goodenough (Community Ecology, 2025)

Temperature synchronizes temporal variation in laying dates across European hole‐nesting passerines - Stefan J. G. Vriend; Vidar Grøtan; Marlène Gamelon; Frank Adriaensen; Markus P. Ahola; Elena Álvarez; Liam D. Bailey; Emilio Barba; Jean‐Charles Bouvier; Malcolm D. Burgess; Andrey Bushuev; Carlos Camacho; et al. (Ecology, 2023)
Identifying the environmental drivers of variation in fitness‐related traits is a central objective in ecology and evolutionary biology. Temporal fluctuations of these environmental drivers are often synchronized at large spatial scales. Yet, whether synchronous environmental conditions can generate spatial synchrony in fitness‐related trait values (i.e., correlated temporal trait fluctuations across populations) is poorly understood. Using data from long‐term monitored populations of blue tits ( Cyanistes caeruleus , n = 31), great tits ( Parus major , n = 35), and pied flycatchers ( Ficedula hypoleuca , n = 20) across Europe, we assessed the influence of two local climatic variables (mean temperature and mean precipitation in February–May) on spatial synchrony in three fitness‐related traits: laying date, clutch size, and fledgling number. We found a high degree of spatial synchrony in laying date but a lower degree in clutch size and fledgling number for each species. Temperature strongly influenced spatial synchrony in laying date for resident blue tits and great tits but not for migratory pied flycatchers. This is a relevant finding in the context of environmental impacts on populations because spatial synchrony in fitness‐related trait values among populations may influence fluctuations in vital rates or population abundances. If environmentally induced spatial synchrony in fitness‐related traits increases the spatial synchrony in vital rates or population abundances, this will ultimately increase the risk of extinction for populations and species. Assessing how environmental conditions influence spatiotemporal variation in trait values improves our mechanistic understanding of environmental impacts on populations.

Behavioural patterns in zoo-housed Humboldt penguins (Spheniscus humboldti) revealed using long-term keeper-collected data: Validation of approaches and improved husbandry - Anne E. Goodenough; Amy Sewell; Katie McDonald (Applied Animal Behaviour Science, 2023)

Learning from the past: opportunities for advancing ecological research and practice using palaeoecological data - Anne E. Goodenough; Julia C. Webb (Oecologia, 2022)

Comparing the effectiveness of camera trapping, driven transects and ad hoc records for surveying nocturnal mammals against a known species assemblage - Adam G. Hart; Melissa Dawson; Richard Fourie; Lynne MacTavish; Anne E. Goodenough (Community Ecology, 2022)

Vegetation community changes in European woodlands amid a changing climate: a palaeoecological modelling perspective - Julia C. Webb; Anne E. Goodenough (Community Ecology, 2021)

Like mother like nest: similarity in microbial communities of adult female Pied Flycatchers and their nests - Anne E. Goodenough; Bethan Stallwood; Shantelle Dandy; Thomas E. Nicholson; Hannah Stubbs; David G. Coker (Journal of Ornithology, 2017)

Managing calcareous grassland for the declining Duke of Burgundy Hamearis lucina butterfly: effects of grazing management on Primula host plants - Anne E. Goodenough; Matthew H. Sharp (Journal of Insect Conservation, 2016)

Recommendations on the Development of a Bioanalytical Assay for 4β-Hydroxycholesterol, an Emerging Endogenous Biomarker of CYP3A Activity - Anne-Françoise Aubry; Brian Dean; Ulf Diczfalusy; Angela Goodenough; André Iffland; James McLeod; Naidong Weng; Ziping Yang (The AAPS Journal, 2016)

Biodiversity in urban gardens: Assessing the accuracy of citizen science data on garden hedgehogs - Rachel L. Williams; Richard Stafford; Anne E. Goodenough (Urban Ecosystems, 2015)

Correlates of vulnerability to climate-induced distribution changes in European avifauna: habitat, migration and endemism - Anne E. Goodenough; Adam G. Hart (Climatic Change, 2013)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

What prevents phenological adjustment to climate change in migrant bird species? Evidence against the “arrival constraint” hypothesis - Anne E. Goodenough; Adam G. Hart; Simon L. Elliot (International Journal of Biometeorology, 2011)

Is adjustment of breeding phenology keeping pace with the need for change? Linking observed response in woodland birds to changes in temperature and selection pressure - Anne Elizabeth Goodenough; Adam G. Hart; Richard Stafford (Climatic Change, 2010)